An adaptive minimum bit-error decision-feedback equalizer for UWB systems - Chung, Gwo Chin; Alias, Mohamad Yusoff; Chuah, Teong Chee (The Institute of Electronics, Information and Communication Engineers, 2007)
Due to the extremely short pulse duration, ultra wideband (UWB) signals entail long impulse responses that cause severe inter-symbol interference (ISI). In this paper, we propose a low-complexity equalizer based on the minimum bit error rate (MBER) criterion for ISI mitigation in realistic UWB channels. Results showed that the proposed equalizer with shorter filter length and same level of complexity can achieve better performance as compared to equalizers based on the minimum mean square error (MMSE) criterion.